2021
DOI: 10.1093/brain/awab252
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial alternating current stimulation for treating depression: a randomized controlled trial

Abstract: Treatment of depression with antidepressants is partly effective. Transcranial alternating current stimulation can provide a non-pharmacological alternative for adult patients with major depressive disorder. However, no study has used the stimulation to treat first-episode and drug-naïve patients with major depressive disorder. We used a randomized, double-blind, sham-controlled design to examine the clinical efficacy and safety of the stimulation in treating first-episode drug-naïve patients in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 37 publications
1
53
0
Order By: Relevance
“…From 6353 records, 12 research papers were included in this review. 3,10,13,[22][23][24][25][26][27][28][29][30] All studies were randomised-controlled trials. This process is detailed in the PRISMA flowchart in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From 6353 records, 12 research papers were included in this review. 3,10,13,[22][23][24][25][26][27][28][29][30] All studies were randomised-controlled trials. This process is detailed in the PRISMA flowchart in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Among individuals with depression, a total of 122 participants were included in the meta-analysis (Figure 3), with 62 in the intervention group and 60 in comparators from three studies. 10,25,30 An SMD of 1.14 (95% CI: 0.10, 2.18) (random effects) with notable heterogeneity (I2 = 72%) were found in the TACS compared to the control group. Of note, Alexander et al 10 randomised 32 patients with depression to receive 40-min sessions of either TACS at 10 Hz or 40 Hz or sham stimulation for five consecutive days.…”
Section: Depressionmentioning
confidence: 99%
“…The current of 15 mA used in 3 out of 4 RCTs (75%, 3/4) ( 9 – 11 ) in this meta-analysis was higher than that used in previous reports ( 8 , 30 32 ). Therefore, it remains unclear whether a smaller current or lower frequency can have dramatic antidepressant efficacy ( 10 ). Importantly, both alpha-tACS ( 8 , 33 ) and gamma-tACS ( 6 , 34 ) can effectively ameliorate depressive symptoms of MDD, suggesting that there are some specific gamma or alpha frequencies or other unknown frequencies that can significantly improve the symptoms of MDD ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although four recent randomized, double-blind, controlled trials (RCTs) ( 8 11 ) have examined the feasibility, efficacy and safety of tACS in treating adult patients with MDD, the findings have been inconsistent. Two RCTs consistently reported that tACS could significantly improve depressive symptoms in first-episode drug-naïve patients suffering from MDD ( 10 , 11 ). However, in Alexander et al’s ( 8 ) study, a negative finding was observed when comparing three different conditions (10 Hz-tACS, 40 Hz-tACS and sham tACS).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike tDCS, which uses direct current, tACS involves applying alternating currents on the scalp to stimulate the cortex and regulate its excitability. tACS appears to have a significant antidepressant effect when current is applied over the frontal region and both mastoid regions in an 8-week protocol [23]. The left dlPFC plays a key role in positive emotions and it is sometimes affected by disorders that lead to increased alpha oscillations in EEG.…”
Section: Non-invasive Approachesmentioning
confidence: 99%